1997
DOI: 10.1177/0093650297024006007
|View full text |Cite
|
Sign up to set email alerts
|

Survivors' Information Seeking Following a Reduction in Workforce

Abstract: Although research on downsizing emphasizes surviving employees' reactions to organizational change, little attention is given to survivors' attempts to meet their information needs. This study of a national insurance company examines employees' information-seeking behaviors prior to and following a permanent reduction in force (RIF). Results indicate that an RIF (a) increases survivors' information deprivation and job insecurity and (b) is associated with the increased use of certain information-seeking strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…Consider alternatives Feldman and Leana, 1994;Cameron et al, 1991;Cameron, 1994;Allen, 1997 Allow time for analysis Cameron, 1994;Freeman, 1994;de Meuse et al, 1994;Burke and Nelson, 1998;Skarlicki, 1998 Leadership Cameron et al, 1991;Cameron, 1994;Freeman, 1994;Mansour-Cole and Scott, 1998 Employee involvement Cameron et al, 1991;Cameron, 1994;Suris;Cascio, 1993;Freeman, 1994;Mishra and Spreitzer, 1998 Employees understand reasons Cameron et al, 1991;Cameron, 1994;Feldman and Leana, 1994;Smeltzer and Zener, 1992;Schweiger and DeNisi, 1991 Use accurate measurement Cameron, 1994;Brockner, 1993 tools Communication of message De Meuse et al, 1994;Mansour-Cole and Scott, 1998;Casey et al, 1997;Johnson et al, 1996;Hopkins and Hopkins, 1999;Schweiger and DeNisi, 1991 An environment of trust Bies, 1987;Bies and Moag;Brockner et al, 1990;Greenberg, 1990;Shapiro et al, 1994;Mishra et al, 1998;Mone, 1997 Give advance notice Feldman and Leana, 1994;Smeltzer and Zener, 1992;…”
Section: Effective Practicementioning
confidence: 99%
“…Consider alternatives Feldman and Leana, 1994;Cameron et al, 1991;Cameron, 1994;Allen, 1997 Allow time for analysis Cameron, 1994;Freeman, 1994;de Meuse et al, 1994;Burke and Nelson, 1998;Skarlicki, 1998 Leadership Cameron et al, 1991;Cameron, 1994;Freeman, 1994;Mansour-Cole and Scott, 1998 Employee involvement Cameron et al, 1991;Cameron, 1994;Suris;Cascio, 1993;Freeman, 1994;Mishra and Spreitzer, 1998 Employees understand reasons Cameron et al, 1991;Cameron, 1994;Feldman and Leana, 1994;Smeltzer and Zener, 1992;Schweiger and DeNisi, 1991 Use accurate measurement Cameron, 1994;Brockner, 1993 tools Communication of message De Meuse et al, 1994;Mansour-Cole and Scott, 1998;Casey et al, 1997;Johnson et al, 1996;Hopkins and Hopkins, 1999;Schweiger and DeNisi, 1991 An environment of trust Bies, 1987;Bies and Moag;Brockner et al, 1990;Greenberg, 1990;Shapiro et al, 1994;Mishra et al, 1998;Mone, 1997 Give advance notice Feldman and Leana, 1994;Smeltzer and Zener, 1992;…”
Section: Effective Practicementioning
confidence: 99%
“…They expressed the need for true and honest participation throughout the entire process, instead of which they thought that there had been too little participation and no opportunity for them to contribute to any decision-making. The results of a study undertaken by Casey, Miller and Johnson (1997) revealed that downsizing appeared to heighten the perception of information deprivation and altered information-seeking patterns at work.…”
Section: Communication During the Changementioning
confidence: 99%
“…Companies undergoing the process of downsizing, mergers, acquisitions, and restructuring are fertile ground for the rumor mill. Casey et al (1997) found that employees relied on third parties for information concerning the workplace in times of transition. This results in "water cooler" talk that is often inaccurate and anxiety provoking for the employee.…”
Section: Implications For Counselorsmentioning
confidence: 99%